Opportunities for the further development of the Safety Case for deep geological repositories by transdisciplinary research – FEP catalogs and scenario development - Ebeling, Marcel; Heiermann, Martina; Röhlig, Klaus-Jürgen (Frontiers in Nuclear Engineering, 2025)
In the TRANSENS research project (2019–2025), large-scale transdisciplinary research on nuclear waste management is being conducted for the first time in Germany. Transdisciplinary in this context means that non-specialists and practice actors are systematically involved in developing and addressing research questions. One out of four TRANSENS research topics is addressing optimization potential for the Safety Case (SC) for Deep Geological Repositories (DGR) for nuclear waste. Seven workshops on this topic were held with three working groups, which differed from one another in terms of their types of knowledge. The work focused on the area of FEP (features, events, and processes) and scenarios. It also shows how objections and optimization proposals for safety cases differ between the various transdisciplinary working groups. Accessibility of SC content was identified as a fundamental area for improvement. Summaries of the report that are appropriate for various target audiences were called for, as was the inclusion of experts from outside the established SC community. The use of digital presentations and communication options was examined in detail. Regarding FEP processing, matrix forms of representation were discussed which, in addition to representing general dependencies, can also depict the strength of these dependencies. There were also proposals for the use of a morphological box to achieve this goal and to be able to create scenarios from FEP. Suggestions were made as to when FEP should be excluded from catalogs, when scenarios can be discarded and how these processes could be documented. To find previously unknown FEP, ideas were put forward regarding a reward system through which the general public could contribute to the completeness of the FEP catalog. In all workshops, promising and valuable results (e.g., criticisms, ideas) were achieved through transdisciplinary research. In TRANSENS, it was proven that the participation of non-experts in research can lead to substantive and in-depth suggestions for improvement. This also means that meaningful contributions based on participatory research are possible in broad participatory processes such as the German site selection procedure. It remains to be seen to what extent the results obtained in TRANSENS will be considered in the preparation of the future German Safety Cases.